Enhanced Breast Cancer Treatment Using Orlistat-Loaded Lipid-Polymer Hybrid Nanoparticles: Formulation, Characterization and Evaluation - Snehalatha, G.; Pashikanti, Shailaja (Journal of Neonatal Surgery, 2025)
Breast cancer continues to be a significant global health concern, prompting the development of advanced drug delivery systems to improve therapeutic effectiveness and minimize adverse effects. Lipid-polymer hybrid nanoparticles (LPHNPs) offer a promising approach by combining the benefits of both liposomes and polymeric nanoparticles, thereby improving drug solubility, bioavailability, and controlled release. This study aimed to develop and optimize Orlistat-loaded LPHNPs (ORL-LPHNPs) using soya lecithin, Eudragit RLPO, and Tween 80 via nanoprecipitation. Various formulations (LPHNP1-LPHNP8) were assessed based on various parameters including particle size, polydispersity index (PDI), zeta potential, entrapment efficiency (EE), and drug loading capacity (DLC).. Among the formulations, LPHNP8 exhibited optimal characteristics, with a particle size of 128±2.7.2 nm, PDI of 0.112±0.09, zeta potential of -33±2.1 mV, EE of 92.07±1.6%, and DLC of 55.24±1.7%. In vitro drug release studies indicated a sustained release pattern, best fitting the Higuchi and Korsmeyer- Peppas models, suggesting a diffusion-controlled release mechanism. Cytotoxicity studies against MCF-7 and MDA-MB-231 breast cancer cell lines exhibited enhanced anticancer efficacy of ORL-LPHNPs compared to free orlistat. Stability studies further confirmed the formulation's robustness over six months. These findings highlight the potential of ORL- LPHNPs as an effective nanocarrier system for breast cancer treatment, warranting further in vivo investigations.